Familial hypercholesterolaemia in Greek females. An epidemiological study - Chasioti, Georgia; Vasiliadis, Ioannis; Rovina, Nikoletta; Dimopoulou, Ioanna; Lagiou, Pagona; Siempos, Elias; Orfanos, Stylianos; Kotanidou, Anastasia (Health & Research Journal, 2025)
Introduction: Cardiovascular diseases are the leading cause of death worldwide. One of the risk factors for cardiovascular diseases is dyslipidemia, defined as the imbalance of lipids in the blood. Familial hypercholesterolemia (FH) is a genetic disorder of lipoprotein metabolism characterized by high levels of total cholesterol in plasma with harmful cardiovascular consequences starting in childhood. Aim: The aim of the present study was to explore the frequency of familial hypercholesterolemia in the female population of Greece. Material and Method: This is a cross-sectional observational study, in which individuals of Greek origin, residing in Greece, were selected. The study sample consisted of 1578 individuals. Data analysis was performed with IBM SPSS 21.0. Results: The mean age of the women was 48.3 years. The prevalence of FH was 1.9%, with 1.8% of women having a probable diagnosis of FH and 0.1% having a definite diagnosis of FH. Familial hypercholesterolemia was more common in women with artery hypertension (p<0.001), diabetes mellitus (p=0.01) and coronary artery disease (p<0.001). Familial hypercholesterolemia was more common in older women (p<0.001) and with a higher body mass index (p=0.02). Conclusions: Optimal screening and diagnosis of FH are of primary importance for the prevention of premature cardiovascular events. Management of patients with FH requires an interprofessional approach, including primary care providers, cardiologists, endocrinologists, dietitians, pharmacists, and nurses, to improve outcomes.